THE DEVELOPMENT OF NATURAL CHEMICAL SUPPLEMENTARY BOOKS BASED ON LOCAL CONTENT ON PREMNA GENUS PLANTS AS ANTIMICROBIAL - Isti`anah, Isti`anah; Hadiarti, Dini; Kurniati, Tuti (Jurnal Pendidikan Matematika dan IPA, 2019)
Natural Chemistry Learning Resources in the form of PowerPoints, scientific journals and books have not accommodated the needs of students. This research aims to provide natural chemical supplement books on the Premna genus as a source of antimicrobial metabolites that are feasible to use based on aspects of validity and practicality. The development model utilized in this study is the Dick and Carey model which includes: identifying learning objectives, analyzing learning, analyzing learners and contexts, formulating specific learning goals, developing assessment instruments, developing learning strategies, developing and selecting teaching materials, designing and developing formative evaluation, and revising the product. The researcher applied research techniques in the form of interviews and observations. The tools used in this research were interview guidelines, student and lecturer response questionnaires, and practice questions in groups. Based on the results of the assessment by material experts and media specialists, this teaching material has a validity value of 91.6% and the practicality of individual trials is 84.51% and small group trials are 76.39%.ABSTRAKPembelajaran Kimia Bahan Alam terdapat sumber belajar berupa powerpoint, jurnal ilmiah dan buku belum mengakomodir kebutuhan mahasiswa. Penelitian ini bertujuan untuk menghasilkan Buku suplemen Kimia Bahan Alam Pada Tanaman Genus Premna Sebagai Sumber Metabolit Antimikroba yang layak digunakan berdasarkan aspek kevalidan dan kepraktisan. Model pengembangan yang digunakan dalam penelitian ini adalah model Dick and Carey meliputi: mengidentifikasi tujuan pembelajaran, melakukan analisis pembelajaran, menganalisis pembelajar dan konteks, merumuskan tujuan pembelajaran khusus, mengembangkan instrumen penilaian, mengembangkan strategi pembelajaran, mengembangkan dan memilih bahan ajar, merancang dan mengembangkan evaluasi formatif, dan melakukan revisi produk. Teknik yang digunakan meliputi wawancara dan observasi. Alat yang digunakan adalah pedoman wawancara, angket respon mahasiswa dan dosen serta soal latihan dalam kelompok. Berdasarkan hasil penilaian oleh ahli materi dan ahli media memiliki nilai kevalidan sebesar 91,6% dan kepraktisan uji coba perorangan sebesar 84,51% serta uji coba kelompok kecil sebesar 76,39%.Kata Kunci: Antimikroba, Buku suplemen, Dick and Carey, Tanaman Genus Premna.